Quasi Moyamoya Disease: Case report and literature review - Neupane, Srijana; Karki, Karuna Tamrakar (Eastern Green Neurosurgery, 2021)
Quasi moyamoya disease is the unilateral form of typical moyamoya disease which is associated with acute or chronic stages of inflammatory diseases. Here, I present 21-year-old boy presented with sudden onset of weakness of right sided limbs following physical workout, had acute ischemic infarction of left internal capsule in diffusion restriction MR image and unilateral steno- occlusive changes of terminal portion of left internal carotid artery was noted in digital subtraction angiography.